Affektpoetiken des New Hollywood Suspense, Paranoia und Melancholie - Lehmann, Hauke (Cinepoetics, 2016)
How do spectators become emotionally involved in cinema? Starting from this question, the book suggests an original view about a critical period in United States film history. In a detailed analysis of individual films, an image emerges of a complex interplay between three affective modes - suspense, paranoia, and melancholy - which draw the spectators to reflect in unique ways about contradictions in their own feelings.